IMPLEMENTATION OF THE EDAS METHOD IN SELECTING INVESTMENT IN THE AGRICULTURAL SECTOR - Ilman Kadori; Susi Widyastuti; Miswadi Miswadi; Nofie Anggraini (TEKNOKOM, 2023)
Capital is one of the most important things in any business activity that will be carried out. Capital includes capital before planting, planting period until harvest time arrives and post-harvest. Because of the large number of farmers in Kuningan district, the Kuningan district Food Security and Agriculture Agency needs investors to help the farmers. In this study designing and building applications for selecting investments in the agricultural sector using a decision support system with the EDAS method. EDAS is a multi-criteria decision-making method based on the AS score. The data used is data from direct interviews with farmers to determine criteria, sub criteria and alternatives. The criteria include land area, capital, harvest period, yields, and selling price. The alternatives include the names of the farmers, namely Tati, Niryo, Odah, Umin, and Tarwa, as well as types of farming, such as chili, shallots, rice, corn, and peanuts. From the results of the overall calculation of this study, it shows that the EDAS method produces the best choice for Tati farming with the type of chili farming. This research produces a web-based application that can be used by farmers and investors and furthermore, it can be developed into an Android or mobile-based application. The goal is to make it easier for investors to find and choose the best farms to invest in.